“Seeds for Needs” experience to improve diversity, nutrition and crop productivity - Kidane, Yosef Gebrehawaryat; Hailemariam, Bogale Nigir; Fadda, Carlo (2022)
The agricultural industry in Ethiopia is dominated by smallholder farming and rain-fed food production systems that are struggling with dwindling diversity and expanding mono- cropping. In order to address diversity, food security, and nutrition, sustainable agricultural production systems must place a greater emphasis on the efficient protection and management of biodiversity and ecosystem services. Growing multiple crops in a region is referred to as crop diversification. It can be achieved by introducing new crop species or varieties, as well as by altering the current cropping system. Typically, it might refer to incorporating extra crops into an already-existing rotation. Our seeds for needs experience will play an important role in enabling agriculture to improve crop productivity, nutrition and crop diversity productivity. Together with Ethiopian and international partners, Bioversity International has been conducting a crowdsourcing methodology and crop improvement strategy under the name "seeds for needs" since 2010 in order to comprehend and study the potential of these varieties in underserved areas and to improve the resilience of the communities where these varieties are grown. The main objective was to provide variation so that farmers could adjust to climate change. The Seeds for Needs Initiative, which leverages the genetic diversity already present to discover traits for adaptation to climate change, has been successfully implemented by Bioversity International. With the help of farmers, particularly women farmers, Seeds for Needs uses a participatory approach to choose a set of crops and varieties that will be further tested under their farming conditions using a crowdsourcing technique. The registration of two varieties in the Tigray region, development of more than 6000 recombinant inbreed lines and their adoption by smallholder farmers in Tigray, Amhara, and Oromia, and a number of scientific paper publications that highlight the most important traits of these varieties—including their high grain and biomass yield in marginal environments, resistance to diseases, and adaptability to climatic conditions that change from year to year—are among the most significant outcomes of these studies